A rare case report of combined metformin-associated lactic acidosis and diabetic ketoacidosis - Yudara Kularathne; Shaun Goh; Sohil Pothiawala (SpringerOpen, 2022)
Abstract Background Triad of diabetic ketoacidosis (DKA) comprises of hyperglycemia with serum glucose > 11 mmol/L, high anion gap metabolic acidosis and ketonemia. Hyperlactemia is often noted in patients with DKA. Metformin use is one of the risk factors of hyperlactemia, resulting in high anion gap metabolic acidosis, known as metformin associated lactic acidosis (MALA). This report is of a 60-year-old woman with type 2 diabetes mellitus who presented with combined metformin-associated lactic acidosis MALA and DKA. Case presentation A 60-year-old diabetic female presented to the emergency department with complaints of abdominal pain, vomiting and diarrhea. She was on metformin for the last 10 years, but despite compliance to medications, her HbA1c was 14.1. With an aim to improve her glycemic control, linagliptin 5 mg once a day was added 1 month ago. Initial investigations in ED including arterial blood gas analysis revealed metabolic acidosis, ketosis, hyperlactemia, and acute kidney injury. In view of metabolic acidosis and ketosis with elevated blood glucose level, she was diagnosed to have DKA. Compared to isolated DKA, patients with combined MALA and DKA have severe metabolic acidosis, a greater degree of hyperlactatemia but less extensive ketoacidosis. Hence, she was diagnosed to have combined MALA and DKA. She was admitted to intensive care unit and treated with intravenous fluids, insulin infusion, and continuous renal replacement therapy. Her metabolic acidosis, hyperlactemia, and kidney injury resolved and she was discharged well. Conclusion This report has shown the importance of rapid diagnosis and management of the rare and challenging diagnosis of combined MALA and DKA. The main goal of therapy is preventing hyperglycemia and ketosis, resolution of metabolic acidosis, and removal of accumulated metformin using intensive therapies like aggressive fluid resuscitation and early initiation of renal replacement therapy. Adjustment of dose of medications is needed to avoid this complication.